Intra‐Aortic Balloon Pump as a Bridge to Durable Left Ventricular Assist Device - Brown, Matthew A.; Sheikh, Farooq H.; Ahmed, Sara; Najjar, Samer S.; Molina, Ezequiel J. (Journal of the American Heart Association, 2021)
Left ventricular assist devices (LVAD) are increasingly being used as destination therapy in patients with Stage D heart failure. It has been reported that a majority of patients who receive a durable LVAD (dLVAD) present in cardiogenic shock due to decompensated heart failure (ADHF‐CS). As it stands, there is no consensus on the optimal management strategy for patients presenting with ADHF. Bridging with intra‐aortic balloon pumps (IABPs) continues to be a therapeutic option in patients with hemodynamic instability due to cardiogenic shock. The majority of data regarding the use of IABP in cardiogenic shock come from studies in patients presenting with acute myocardial infarction with cardiogenic shock and demonstrates that there is no benefit of routine IABP use in this patient population. However, the role of IABPs as a bridge to dLVAD in ADHF‐CS has yet to be determined. The hemodynamic changes seen in acute myocardial infarction with cardiogenic shock are known to be different and more acutely impaired than those presenting with ADHF‐CS as evidenced by differences in pressure/volume loops. Thus, data should not be extrapolated across these 2 very different disease processes. The aim of this review is to describe results from contemporary studies examining the use of IABPs as a bridge to dLVAD in patients with ADHF‐CS. Retrospective evidence from large registries suggests that the use of IABP as a bridge to dLVAD is feasible and safe when compared with other platforms of temporary mechanical circulatory support. However, there is currently a paucity of high‐quality evidence examining this increasingly important clinical question.